Synthesis, Molecular Structure and Antibacterial Activity of Spiro[2,2']indane-1',3'-dione-3-(o-chloro)phenyl-4-nitro Pyrrolizidine - Sun, Guo-Xin; Miao, Yan-Qing (Asian Journal of Chemistry, 2015)
Spiro[2,2']indane-1',3'-dione-3-(o-chloro)phenyl-4-nitro pyrrolizidine was synthesized by 1,3-dipolar cycloaddition reaction. It was characterized by NMR, MS and single-crystal X-ray diffraction. It crystallizes in the triclinic space group, P-1, with unit cell dimensions a = 7.6074(4) Å, b = 9.7454(5) Å and c = 12.6538(7) Å, a = 85.313(2)º, b = 84.217(2)º, g = 86.571(2)º and Z = 2. It was screened for antibacterial activity against oilfield water-borne bacteria and it showed good to moderate activity against sulfate reducing bacteria.